KEKUATAN PEMBUKTIAN AIR MANI SEBAGAI ALAT BUKTI PETUNJUK TINDAK PIDANA PEMERKOSAAN - Andris Amir Al Ghifari (2021)
The background in working on this journal is to raise the material, namely semen which is used as an object of proof of acts of violent crime, namely the crime of rape, because in some cases the investigative team has difficulty in finding evidence that can be used as a reference in solving rape cases and in some cases In cases in the field, investigators only found the remaining sperm fluid that was left or scattered at the scene where the crime of rape occurred. The purpose of conducting research in the journal that will be discussed this time is to explain the concepts and procedures carried out by investigators in the form of sampling and conducting research on the samples obtained in this case which became the main topic, namely sperm samples which were suspected to be the result of the crime of rape. In proving cases of sexual intercourse is not easy because in most of these incidents there are no witnesses, the lack of evidence and various other difficulties. The history and physical examination carried out by the examining physician have considerable doubtful values. From the sampling to the research carried out by the investigator team and assisted by the medical forensic team, it can be concluded that in this evidence semen can be used as evidence for a criminal act, namely rape.